Perancangan Fasilitas Duduk Sebagai Sarana Penggunaan Smart Phone dan Game Mobile - Alfonsus Reynaldo Louis; Grace Mulyono (Intra, 2019)
In this design, student observe user’s activities when sitting and playing smart phone with correct posture, even in a long periods. With guide form RULA, student found the most ergonomic sitting posture when playing games and using smart phones, as a base of the design to make the most comfortable experience while using the facility. This design emphazise on ergonomic measurement in the neck and arm rest area to make comfortable experience when playing smart phones. Overall, this thesis provide readers to understand the correct sitting posture based on RULA guidelines and can be used as a reference for the community.